DEVELOPING STUDENTS’ SOFT SKILLS: INTEGRATING UKRAINE’S NON-FORMAL EDUCATION INTO THE EUROPEAN EDUCATIONAL SPACE - Boiko, Anna (Theoretical and Methodical Problems of Children and Youth Education, 2022)
In the conditions of a full-scale war against Ukraine, the activities of educational institutions, including non-formal ones, are directed not only to the provision of educational services, but to the psychological, pedagogical and social support of children and families in crisis conditions. Granting Ukraine the status of a candidate for EU member actualizes the need to bring the field of education into compliance with the standards and recommendations of the European Union, especially non-formal education. The aim of the article is to determine the main direction of developing students’ soft skills in the context of the integration of non-formal education in Ukraine into the European educational space. The theoretical and empirical research methods were used to achieve the research objectives: analysis and generalization of scientific studies and legal documents in order to determine the key points of European education; survey on the organization of the educational process in institutions of out-of-school education under martial law; systematization and comparison of data obtained in order to identify the main directions of formation of students’ soft skills in non-formal education. According to the results of a survey on the organization of the educational process in institutions of out-of-school education under martial law, forming students’ soft skills such as critical thinking, the ability to manage one’s emotions constructively, the ability to assess risks and make decisions was clarified as a priority. It is concluded that there is a need to improve and bring to European educational standards the content of non-formal education, learning technologies, the formation of soft skills in children and youth necessary for a modern citizen of the civilized world, relevant for the post-war recovery of the country. The practical significance of the research is that its materials can be used to develop educational programs for out-of-school education, in the system of professional teacher training and pedagogical practice of students in accordance with the integration of non-formal education into the European educational space. Future research should consider the potential effects of developing students’ soft skills in the context of the integration of non-formal education in Ukraine into the European educational space more carefully.